2018
DOI: 10.1128/jvi.01022-18
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus MicroRNA miR-BART5-3p Inhibits p53 Expression

Abstract: Epstein-Barr virus (EBV) is the first human virus found to encode many microRNAs. It is etiologically linked to nasopharyngeal carcinoma and EBV-associated gastric carcinoma. During the latent infection period, there are only a few EBV proteins expressed, whereas EBV microRNAs, such as the BamHI-A region rightward transcript (BART) microRNAs, are highly expressed. However, how these BART miRNAs precisely regulate the tumor growth in nasopharyngeal carcinoma and gastric carcinoma remains obscure. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 65 publications
1
61
0
Order By: Relevance
“…EBV latent infection is an important causative factor in the development of related cancers such as NPC (Dittmer et al, 2008;Zheng et al, 2014Zheng et al, , 2018, although the mechanism is largely unclear. Viral replication and genome maintenance in host cells are important for the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…EBV latent infection is an important causative factor in the development of related cancers such as NPC (Dittmer et al, 2008;Zheng et al, 2014Zheng et al, , 2018, although the mechanism is largely unclear. Viral replication and genome maintenance in host cells are important for the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…BART3-3p plays an important role in inhibiting the senescence of GC cells by targeting TP53 [134]. As for apoptosis, it was reported that BART5-3p directly targets TP53, leading to acceleration of the cell cycle progress and inhibition of cell apoptosis [135]. Besides, EBV encoded miR-BART5 could target p53 upregulated modulator of apoptosis (PUMA), which is a proapoptotic protein belonging to the Bcl-2 family, to counteract apoptosis and promote cellular survival [136].…”
Section: Promoting Roles Of Virologic Genes In Gc Pathogenesismentioning
confidence: 99%
“…Activates NF-κB-survivin pathway to rescue EBV-infected epithelial cells from serum deprivation [122] Regulates cyclin E expression and S phase cell ratio [123] Elevates mitochondrial fission and promotes cellular migration through Notch pathway [124] Downregulates HLA to evade immune response [125] Activates phosphatidylinositol 3-kinase/Akt pathways to mediate transformation and inhibits transforming growth factor-beta 1-induced apoptosis [126,127] Promotes cell malignant by inducing epigenetic changes of host genome [129] Upregulates miR-155-5p, and targets Smad2 and p-Smad2 to regulate TGF-β pathway [128] miR-BARTs miR-BART9 decreases E-cadherin expression and upregulates proliferation [133] miR-BART3-3p inhibits the senescence of gastric cancer cells by targeting TP53 [134] miR-BART5-3p targets the tumor-suppressor gene TP53, leading to acceleration of the cell cycle progress and inhibition of cell apoptosis [135] miR-BART5 targets PUMA, counteracts apoptosis and promotes cellular survival [136] miR-BART9, 11, and 12 downregulate Bim expression [137] miR-BART4-5p suppresses the proapoptotic protein Bid to regulate apoptosis [138] miR-BART20-5p interacts with 3'UTR of BAD to contribute to tumorigenesis [139] miR-BART16 suppresses type I IFN signaling [140] with clinical outcome. MSI subtype has the best prognosis and lowest recurrence rate followed by MSS/TP53 + and MSS/TP53 − , while the MSS/EMT subtype demonstrates the worst prognosis and highest recurrence rate among the four subtypes.…”
Section: Ebermentioning
confidence: 99%
“…We recently reported another BART microRNA, BART5-3p, that can directly target TP53 by combining with TP53 3Ј-UTR, thereby promoting the progression of EBV-positive epithelial tumors (38). Unlike BART5-3p, BART3-3p binds to the TP53 CDS region but not 3Ј-UTR (Fig.…”
Section: Ebv-mir-bart3-3p Regulates Gastric Cancer Senescencementioning
confidence: 99%